Coping Religious Lonely Elder Death Anxiety - Juaini, Evi; Triyono, Triyono (Indonesian Journal of Islamic Education and Local Culture, 2024)
This research aims to determine the factors that cause anxiety about facing death and the forms of religious coping used by elderly people who live alone. This research uses a qualitative phenomenological method. Data collection techniques use interviews, observation and documentation. The informants in this research were three elderly Muslims who lived alone in Bibis Kulon village, Surakarta City who were selected using purposive sampling. Data were analyzed using analysis from Miles, Huberman, and Saldana. The results of this research show that there are six factors that cause anxiety about facing death, namely age, ego integrity, self-control, disease diagnosis, experiences related to death, and life that occurs after death. Religious coping used by elderly people who live alone has two forms, namely differing and collaborative. Differing involves the act of surrendering oneself to Allah. Meanwhile, collaborative involves activities such as prayer, dhikr, prayers, reading the Koran, and attending recitations. The use of religious coping helps elderly people who live alone overcome anxiety when facing death which can occur at any time. They believe that death is God's unavoidable destiny.